Implementasi Pembelajaran Berdiferensiasi Menggunakan Model Pembelajaran Problem Based Learning (PBL) Dalam Meningkatkan Hasil Belajar Matematika Kelas IV - Nasrul, Hikmah Setia; Sofwan, Muhammad; Iskandar, Dedi; Wahyuni, Ida (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2024)
This research is motivated by the low mathematics learning outcomes of students. The study aims to improve the mathematics learning outcomes of students by implementing differentiated learning using the Problem-Based Learning model in Class IV of SDN 19 Jambi. This study is a Classroom Action Research consisting of two cycles. Based on the observation results of teacher activities in Cycle I, 78% were categorized as good, and in Cycle II, it increased to 85%. Based on the research data, the test results in the form of evaluation questions to determine student learning outcomes in Cycle I were 57%, and in Cycle II, it increased to 76%. Therefore, it can be concluded that the implementation of differentiated learning using the Problem-Based Learning model can improve the mathematics learning outcomes of Class IV SDN 19 Jambi.